Bisphenol S disrupts opsins gene expression and impairs the light-sensing function via antagonizing TH-TRβ signaling pathway in zebrafish larvae. (February 2023) - Wei, Shuhui; Qiu, Liguo; Ru, Shaoguo; Yang, Yang; Wang, Jun; Zhang, Xiaona
Abstract: Bisphenol S (BPS) is extensively used in "bisphenol A-free" products such as baby bottles. Although the visual toxicity of BPS has been reported, the underlying mechanism was largely unknown. In the present study, zebrafish were exposed to 0, 4 and 400 nM BPS from 2 h post-fertilization (hpf) to 120 hpf to further explore the thyroid disruption mechanism underlying the BPS induced impairment of visual function. The results showed that BPS decreased T3 levels in larval eyes, induced retinal expression of thyroid hormone receptor β (TR β ), and thereby down-regulated the expression of TH-mediated opsin genes ( opn1lw1, opn1lw2, opn1mw1, opn1mw2, opn1mw3, and opn1sw2 ) and impaired subsequent phototransduction pathways, leading to decreased visually mediated phototactic response and body color adaptation but stimulated visual motor response (VMR). Combining exposure of exogenous T3 or 1–850 (antagonist for TR β ) with BPS could partly compensate the inhibited expression of opsin genes ( opn1mw2, opn1lw1, and opn1lw2 ) and alleviate the hyperactivity of larval VMR caused by BPS alone, suggesting that BPS disrupted the opsins expression and also light-sensing function via antagonizing TH-TR β signaling pathway. This study underlined the importance of TH signaling in regulating the proper vision and proposed a novel mechanism for the visual toxicity of BPS.